Penerapan Metode At Taisir Dalam Meningkatkan Hafalan Ayat Al Qur'an Pada Peserta Didik Kelas Ix A Di Pondok Pesantren Tahfidzul Qur'an Assalam Kabupaten Sidrap - Muharram, Muh Firman; Razak, Ahmad; Syahrul, Muhammad (Jurnal Pendidikan Indonesia, 2025)
This study aims to increase the number of memorized Qur’anic verses among Class IX A students at Tahfidzul Qur’an Assalam Islamic Boarding School in Sidrap Regency by applying the At-Taisir method. The method serves not only to enrich knowledge about its use in enhancing Qur'anic memorization but also as a contribution of thought for teachers in meeting student needs and as a guideline for solving classroom learning challenges related to Qur’anic education. The research subjects were 20 students from Class IX A. The research method used was Classroom Action Research (CAR), consisting of two cycles. The procedure followed four stages: planning, action, observation, and reflection. Data collection techniques included observation, interviews, tests, and documentation. The data analysis used both qualitative and quantitative approaches.The implementation of the At-Taisir method was conducted over two cycles. The results showed that it effectively improved students’ Qur’anic memorization skills, as evidenced by the mean score of 83.82 in Cycle I and 93.33 in Cycle II. The At-Taisir method also enhanced active participation and understanding of the material, particularly in the aspects of verse repetition accuracy, memorization consistency, review (murojaah) ability, correct verse recall, and reading fluency, with all 20 students achieving complete success. The At-Taisir method proved effective in increasing students' Qur’anic memorization due to its systematic, gradual approach tailored to individual capabilities. Through two implementation cycles, this method improved students' active participation in the memorization process. Students found it easier to understand and memorize verses as the material was delivered simply and sequentially. Furthermore, the method emphasized repetition and reinforcement of memorization, enabling students to maintain consistency. The students’ ability to review memorized verses also improved, as seen in their accuracy. Significant improvement in average scores and the number of students who met learning objectives confirms that the At-Taisir method effectively enhances both the quantity and quality of Qur’anic memorization.